Leading Condition Of Small Pelagic Resources Based On Data In The State Fisheries Management Area Of The Republic Of Indonesia (Wppnri) 712 And 573 Year 1990 - 2017 East Java Province For Sustainable Management - Tri Djoko Lelono; Muhammad Arif Rahman; Gatut Bintoro; Nita Hellis Setyowati; Nindi Nur Wulandari (Journal of Aquaculture Science, 2021)
Pelagic fish resources have a very important role in regional economic development. The assumption that fish resources are common property so that everyone is free to catch (open access) is a problem with overfishing in East Java waters. The purpose of this study is to determine the superior commodity of small pelagic fish, the status of exploitation of superior  fish resources and to compile a scenario of sustainable management of superior resources. The method in this research is quantitative descriptive method with data analysis used including Location Quotient (LQ), Schaefer (1954), Fox (1970), Walter Hilborn, and programming STELLA (System Thinking, Experimental Learning Laboratory with Animation). The research result of the superior species in the province in the south of East Java) is sardin, while the superior fish in the regency is s Rainbow runner. The status of fisheries at the level of superior fisheries exploitation in South East Java, the level of exploitation of ssrdin fish is 240% with the status of Depleted. Finally, the level of exploitation for s Rainbow runner fish is 689%, which means that they are included in depleted. The scenario of sustainable management of pelagic fisheries for the next 10 years, namely 2018 - 2027 for lemuru fish, the highest biomass reserves will be obtained in 2027, using a fixed effort allocation which has biomass reserves of 179% and the potential value of sustainable reserves of 8,438.48 tonnes. The results showed that the superior commodities of small pelagic fish in North East Java were mackerel fish. The superior fish commodity in the Regency / City is obtained by Finny scad fish. The level of exploitation for mackerel is 127% with the status of Over Exploited, and the level of exploitation for Finny scad is 131% with the status of Over Exploited. The scenario for the management of the superior mackerel commodity, the highest biomass reserve in 2027 is the allowable fishing effort allocation (fJTB) of 129%. Key Words: STELLA ,Superior commodity, Fishery status, Sustainable potential